Fatores determinantes para evasão e permanência de estudantes no ensino superior - Bezerra, Vanessa da Silva (Brasil, 2024)
This study analysed the reasons that influence student dropout and permanence in undergraduate courses at a public Higher Education Institution (HEI) in northern Brazil. An electronic questionnaire was administered to 57 students from the Business Administration, Accountancy and Economics programmes, who were studying between the 3rd and 7th terms. The data was analysed using Bardin's Content Analysis Technique (2016), categorising the factors into Institutional, Individual and Professional. The research revealed that dropout is a complex and multifactorial phenomenon, with emphasis on individual factors such as lack of identification with the course, financial problems and health issues. The ‘Individual’ category was the most representative among the reasons for dropping out, while institutional and professional aspects were also mentioned, albeit less frequently. The reasons for staying, on the other hand, are strongly linked to students' career expectations and future planning. Professional motivation, opportunities for growth in the field of study and appreciation of individual effort were determining factors for students to continue with their courses. Institutional aspects such as financial support also contributed to staying, albeit to a lesser extent.